Skip to main content

Some Hermite–Jensen–Mercer type inequalities for k-Caputo-fractional derivatives and related results

Abstract

In this paper, certain Hermite–Hadamard–Mercer type inequalities are proved via k-Caputo fractional derivatives. We established some new k-Caputo fractional derivatives inequalities with Hermite–Hadamard–Mercer type inequalities for differentiable mapping \(\psi^{(n)}\) whose derivatives in the absolute values are convex.

Introduction

Let \(0< u_{1}\leq u_{2}\leq\cdots\leq u_{n}\) and let \(\mu= (\mu _{1},\mu_{2},\ldots,\mu_{n} )\) be non-negative weights such that \(\sum_{i=1}^{n} \mu_{i}=1\). The famous Jensen inequality [1] states that if ψ is a convex function on the interval \([\theta _{1},\theta_{2} ]\), then

$$ \psi \Biggl( \sum_{i=1}^{n} \mu_{i} u_{i} \Biggr)\leq \Biggl( \sum _{i=1}^{n} \mu_{i} \psi ( u_{i} ) \Biggr) $$
(1)

for all \(u_{i}\in [ \theta_{1},\theta_{2} ]\) and \(\mu_{i}\in [ 0,1 ]\) (\(i=1,2,\ldots,n \)).

In 1883, the Hermite–Hadamard (H-H) inequality was considered the most useful inequality in mathematical analysis. It is also known as the classical H-H inequality.

The Hermite–Hadamard inequality asserts that if \(\psi:J\subseteq{R}\to {R}\) is a convex function defined on J and \(\theta_{1},\theta_{2}\in J\) such that \(\theta_{1}<\theta_{2}\), then

$$ \psi \biggl(\frac{\theta_{1}+\theta_{2}}{2} \biggr) \le\frac{1}{\theta _{2}-\theta_{1}} \int_{\theta_{1}}^{\theta_{2}} \psi(\lambda) \,d \lambda\le \frac {\psi(\theta_{1})+\psi(\theta_{2})}{2}. $$

For recent results related with the Jensen–Mercer inequality, see [14].

Theorem 1

Ifψis a convex function on\([ \theta_{1},\theta_{2} ]\), then

$$ \psi \Biggl( \theta_{1}+\theta_{2}- \sum_{i=1}^{n} \mu _{i} u_{i} \Biggr) \leq\psi ( \theta_{1} ) +\psi ( \theta _{2} ) -\sum_{i=1}^{n} \mu_{i} \psi ( u_{i} ), $$
(2)

\(\forall u_{i}\in [ \theta_{1},\theta_{2} ]\)and all\(\mu _{i}\in [ 0,1 ]\) (\(i=1,2,\ldots,n \)).

Inequality (2) is known as the Jensen–Mercer inequality. Recently, inequality (2) has been studied and generalized in [57].

Fractional calculus was generally a study kept for the best minds in mathematics. The early era of fractional calculus is as old as the history of differential calculus. One generalized the differential operators and ordinary integrals. However, the fractional derivatives have some more basic properties than the corresponding classical ones. On the other hand, besides the smooth requirement, the Caputo derivative does not coincide with the classical derivative [8]. It was introduced in 1967.

In the following, we give the definition of Caputo fractional derivatives (see [911] and the references therein).

Definition 1

Let \(\alpha>0\) and \(\alpha\notin \{ 1,2,3,\dots \}\), \(n= [ \alpha ] +1\), \(\psi\in C^{n} [ \theta_{1},\theta_{2} ] \). The Caputo fractional derivatives of order α are defined as follows:

$$ \bigl( {}^{ c}D_{\theta_{1}^{+}}^{\alpha} \psi \bigr) ( u ) = \frac{1}{\varGamma ( n-\alpha ) } \int_{\theta_{1}}^{u} \frac {\psi^{(n)} ( \lambda ) }{ ( u-\lambda ) ^{\alpha-n+1}} \,d\lambda; \quad u>\theta_{1}, $$

and

$$ \bigl( {}^{ c}D_{\theta_{2}^{-}}^{\alpha} \psi \bigr) ( u ) = \frac{ ( -1 ) ^{n}}{\varGamma ( n-\alpha ) } \int _{u}^{\theta_{2}}\frac{\psi^{(n)} (\lambda ) }{ ( \lambda -u ) ^{\alpha-n+1}} \,d\lambda; \quad u< \theta_{2}. $$

If \(\alpha=n \in \{ 1,2,3,\ldots \}\) and the usual derivatives of ψ of order n exist, then the Caputo fractional derivatives \(( {}^{ c}D_{\theta_{1}^{+}}^{\alpha}\psi ) (u )\) coincide with \(\psi^{(n)} ( u ) \).

In particular, we have

$$ \bigl( {}^{ c}D_{\theta_{1}^{+}}^{0}\psi \bigr) ( u ) = \bigl({}^{ c}D_{\theta_{2}^{-}}^{0} \psi \bigr) ( u ) = \psi ( u ), $$

where \(n=1\) and \(\alpha=0\).

Definition 2

(See [12])

Diaz and Parigun have defined the k-Gamma function \(\varGamma_{k}\), a generalization of the classical Gamma function, which is given by the following formula:

$$ \varGamma_{k} (x) = \lim_{n-\infty} \frac{n! k^{n} (nk)^{\frac {x}{k}}-1}{(x)_{n,k}} k > 0. $$

It is shown that the Mellin transform of the exponential function \(e^{-\frac{t^{k}}{k}} \) is the k-Gamma function given by

$$ \varGamma_{k} (\alpha) = \int_{0}^{\infty} e^{-\frac{t^{k}}{k}} t^{\alpha -1}\, dt. $$

Obviously, \(\varGamma_{k}(x+k)=x \varGamma_{k}(x)\), \(\varGamma(x)=\lim_{k \rightarrow1}\varGamma_{k} (x)\) and \(\varGamma_{k}(x)=k^{\frac{x}{k}-1} \varGamma (\frac{x}{k})\).

Definition 3

([13])

Let \(\alpha>0\), \(k\geq1\) and \(\alpha\notin \{ 1,2,3,\dots \}\), \(n= [\alpha ] +1\), \(\psi\in C^{n} [\theta_{1},\theta_{2} ]\). The right-sided and left-sided Caputo k-fractional derivatives of order α are defined as follows:

$$ \bigl( {}^{ c}D_{\theta_{1}^{+}}^{\alpha,k } \psi \bigr) ( u ) =\frac{1}{k\varGamma_{k} ( n-\frac{\alpha}{k} )} \int_{\theta _{1}}^{u}\frac{\psi^{(n)} ( \lambda )}{ ( u-\lambda )^{\frac{\alpha}{k} -n+1}}\, d\lambda; \quad u> \theta_{1} $$
(3)

and

$$ \bigl( {}^{ c}D_{\theta_{2}^{-}}^{\alpha,k } \psi \bigr) ( v ) =\frac{ ( -1 ) ^{n}}{k\varGamma_{k} ( n-\frac{\alpha }{k} )} \int_{v}^{\theta_{2}}\frac{\psi^{(n)} ( \lambda ) }{ ( \lambda-v )^{\frac{\alpha}{k} -n+1}} \,d\lambda; \quad v< \theta_{2}. $$
(4)

For \(k=1\), Caputo k-fractional derivatives give the definition of Caputo fractional derivatives.

In this article, by using the Jensen–Mercer inequality, we prove Hermite–Hadamard inequalities for fractional integrals and we establish some new Caputo k-fractional derivatives connected with the left and right sides of Hermite–Hadamard type inequalities for differentiable mappings whose derivatives in absolute values are convex.

Throughout the paper, we need the following assumptions.

\(A_{1} = \forall u,v\in [ \theta_{1},\theta_{2} ]\), \(\alpha >0\), \(k\geq1 \) and \(\varGamma_{k} ( \cdot )\) is the k-Gamma function.

Hermite–Hadamard–Mercer type inequalities for Caputo k-fractional derivatives

By using the Jensen–Mercer inequality, Hermite–Hadamard type inequalities can be expressed in Caputo k-fractional derivative form as follows.

Theorem 2

Suppose that if\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a positive function with\(0\leq\theta_{1}<\theta_{2}\)and\(\psi\in C^{n} [ \theta_{1},\theta_{2} ] \). If\(\psi^{(n)}\)is a convex function on\([\theta_{1},\theta_{2}]\)along with the assumptions in\(A_{1}\), then the following inequalities for Caputok-fractional derivatives hold:

$$\begin{aligned} &\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) \\ &\quad\leq\psi^{(n)} ( \theta_{1} )+\psi^{(n)} ( \theta_{2} ) -\frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{2 (v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl({}^{ c}D_{u^{+}}^{\alpha,k } \psi \bigr) ( v ) + ( -1 ) ^{n} \bigl({}^{ c}D_{v^{-}}^{\alpha,k} \psi \bigr) ( u ) \bigr\} \\ &\quad\leq\psi^{(n)} ( \theta_{1} )+\psi^{(n)} ( \theta_{2} ) -\psi^{(n)} \biggl( \frac{u+v}{2} \biggr). \end{aligned}$$
(5)

Proof

Using the Jensen–Mercer inequality, we have

$$ \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \frac{w+z}{2} \biggr) \leq\psi ^{(n)} ( \theta_{1} )+\psi^{(n)} ( \theta_{2} ) -\frac {\psi^{(n)} ( w ) +\psi^{(n)} ( z ) }{2} $$
(6)

for all \(w,z \in [ \theta_{1},\theta_{2} ]\).

Now by change of variables \(w=\lambda u+(1-\lambda)v \) and \(z=(1-\lambda )u+\lambda v \), for all \(u,v\in [ \theta_{1},\theta_{2} ]\) and \(\lambda\in [ 0,1 ] \) in (6), we have

$$\begin{aligned} \begin{aligned} &\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \frac{u+v}{2} \biggr) \\ &\quad\leq\psi^{(n)} ( \theta_{1} )+\psi^{(n)} ( \theta_{2} ) -\frac{\psi^{(n)} ( \lambda u+(1-\lambda)v ) +\psi^{(n)} ( (1-\lambda)u+\lambda v ) }{2}.\end{aligned} \end{aligned}$$

Multiplying both sides by \(\lambda^{n-\frac{\alpha}{k}-1}\) above and then integrating the resulting inequality with respect to λ over \([ 0,1 ]\), we have

$$\begin{aligned} &\frac{1}{ (n-\frac{\alpha}{k} )}\psi^{(n)} \biggl( \theta _{1}+ \theta_{2}-\frac{u+v}{2} \biggr) \\ &\quad\leq\frac{1}{ (n-\frac{\alpha }{k} )} \bigl\{ \psi^{(n)} ( \theta_{1} ) +\psi^{(n)} ( \theta_{2} ) \bigr\} \\ & \quad\quad- \frac{1}{2} \biggl\{ \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \bigl( \psi^{(n)} \bigl(\lambda u+ ( 1-\lambda ) v \bigr) +\psi ^{(n)} \bigl( ( 1-\lambda ) u+\lambda v \bigr) \bigr)\, d\lambda \biggr\} , \end{aligned}$$

hence

$$\begin{aligned} &\psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \frac{u+v}{2} \biggr) \\ &\quad\leq\psi ^{(n)} ( \theta_{1} )+\psi^{(n)} ( \theta_{2} ) \\ &\qquad-\frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{2 (v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl( {}^{ c}D_{u^{+}}^{\alpha,k } \psi \bigr) ( v ) + ( -1 ) ^{n} \bigl( {}^{ c}D_{v^{-}}^{\alpha,k} \psi \bigr) ( u ) \bigr\} \end{aligned}$$

and so the first inequality of (5) is proved.

Now for the proof of second inequality of (5), we first note that if \(\psi^{(n)}\) is a convex function, then for \(\lambda\in [ 0,1 ]\), it gives

$$\begin{aligned} \psi^{(n)} \biggl( \frac{u+v}{2} \biggr) &= \psi^{(n)} \biggl( \frac{\lambda u+ (1-\lambda ) v+ ( 1-\lambda ) u+\lambda v}{2} \biggr) \\ &\leq\frac{\psi^{(n)} ( \lambda u+ (1-\lambda ) v ) +\psi^{(n)} ( ( 1-\lambda ) u+\lambda v ) }{2} . \end{aligned}$$

Multiplying both sides by \(\lambda^{n-\frac{\alpha}{k}-1}\) above and then integrating the resulting inequality with respect to λ over \([ 0,1 ]\), we have

$$\begin{aligned} &\frac{1}{n-\frac{\alpha}{k} } \psi^{(n)} \biggl( \frac{u+v}{2} \biggr) \\ &\quad\leq\frac{1}{2} \biggl\{ \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \bigl( \psi^{(n)} \bigl(\lambda u+ ( 1-\lambda ) v \bigr) +\psi^{(n)} \bigl( ( 1-\lambda ) u+\lambda v \bigr) \bigr)\, d\lambda \biggr\} , \end{aligned}$$

hence

$$ \psi^{(n)} \biggl( \frac{u+v}{2} \biggr) \leq \frac{\varGamma_{k} (n-\frac {\alpha}{k} +k ) }{2 ( v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl({}^{ c}D_{u^{+}}^{\alpha,k } \psi \bigr) ( v ) + ( -1 ) ^{n} \bigl({}^{ c}D_{v^{-}}^{\alpha,k } \psi \bigr) ( u ) \bigr\} . $$

Multiplying by \((-1)\) on both sides, we have

$$ -\frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{2 ( v-u )^{n-\frac{\alpha}{k} }} \bigl\{ \bigl( {}^{ c}D_{u^{+}}^{\alpha,k } \psi \bigr) ( v )+ ( -1 )^{n} \bigl( {}^{ c}D_{v^{-}}^{\alpha,k } \psi \bigr) (u ) \bigr\} \leq- \psi ^{(n)} \biggl( \frac{u+v}{2} \biggr). $$
(7)

Adding \(\psi^{(n)}(\theta_{1})+\psi^{(n)}(\theta_{2})\) in both sides in (7), we get the second inequality of (5). □

Remark 1

If we take \(k=1\) in Theorem 2, then it reduces to Theorem 2 in [14].

Theorem 3

Suppose that if\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a positive function with\(0\leq\theta_{1}<\theta_{2}\)and\(\psi\in C^{n} [ \theta_{1},\theta_{2} ] \). If\(\psi^{(n)}\)is a convex function on\([\theta_{1},\theta_{2}]\)along with the assumptions in\(A_{1}\), then the following inequalities for the Caputok-fractional derivatives hold:

$$\begin{aligned} & \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) \\ &\quad \leq\frac{2^{n-\frac{\alpha}{k}-1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl( {}^{ c}D_{ (\theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) \\ &\qquad+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta _{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta _{1}+\theta_{2}-v ) \bigr\} \\ &\quad\leq\psi^{(n)} ( \theta_{1} ) +\psi^{(n)} ( \theta_{2} ) - \biggl( \frac{\psi^{(n)} ( u ) + \psi^{(n)} ( v ) }{2} \biggr). \end{aligned}$$
(8)

Proof

To prove the first part of the inequality, we use the convexity of \(\psi^{(n)}\),

$$\begin{aligned} \psi^{ ( n ) } \biggl( \theta_{1}+\theta_{2}- \frac {u_{1}+v_{1}}{2} \biggr) &=\psi^{ ( n ) } \biggl( \frac{\theta _{1}+\theta_{2}-u_{1}+\theta_{1}+\theta_{2}-v_{1}}{2} \biggr) \\ &\leq\frac{\psi^{ ( n ) } ( \theta_{1}+\theta _{2}-u_{1} ) +\psi^{ ( n ) } ( \theta_{1}+\theta _{2}-v_{1} ) }{2} \end{aligned}$$

for all \(u_{1}, v_{1} \in[\theta_{1},\theta_{2}]\). Now by writing the variables \(u_{1}=\frac{\lambda}{2}u+\frac{2-\lambda}{2}v \) and \(v_{1}=\frac{2-\lambda}{2}u+\frac{\lambda}{2}v\), for \(u,v\in[\theta _{1},\theta_{2}]\) and \(\lambda\in[0,1]\), we get

$$\begin{aligned} & 2\psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \frac{u+v}{2} \biggr) \\ &\quad\leq\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \biggl(\frac{\lambda}{2}u+\frac {2-\lambda}{2}v \biggr) \biggr) + \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda}{2}v \biggr) \biggr) . \end{aligned}$$

Multiplying both sides by \(\lambda^{n-\frac{\alpha}{k}-1}\) above and then integrating the resulting inequality with respect to λ over \([ 0,1 ]\), we have

$$\begin{aligned} & 2\psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \frac{u+v}{2} \biggr) \int _{0}^{1}\lambda^{n-\frac{\alpha}{k}-1}\,d\lambda \\ &\quad\leq \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \biggl( \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \\ &\qquad +\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{2-\lambda }{2}u+\frac{\lambda}{2}v \biggr) \biggr) \biggr) \,d \lambda, \end{aligned}$$

hence

$$\begin{aligned} & \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) \\ &\quad \leq\frac{2^{n-\frac{\alpha}{k}-1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl({}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) \\ &\qquad+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta _{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta _{1}+\theta_{2}-v ) \bigr\} \end{aligned}$$
(9)

and so the first inequality of (8) is proved.

Now for the proof of second inequality of (5), we first note that if \(\psi^{(n)}\) is a convex function, then for \(\lambda\in [ 0,1 ]\), it yields

$$\begin{aligned} &\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{\lambda}{2}u+\frac {2-\lambda}{2}v \biggr) \biggr) \\ &\quad\leq\psi^{(n)} ( \theta_{1} ) +\psi^{n} ( \theta_{2} ) - \biggl[ \frac{\lambda}{2}\psi^{(n)} ( u ) +\frac{2-\lambda }{2}\psi^{(n)} ( v ) \biggr] \end{aligned}$$
(10)

and

$$\begin{aligned} &\psi^{(n)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac {\lambda}{2}v \biggr) \biggr) \\ & \quad\leq\psi^{(n)} ( \theta_{1} ) + \psi^{(n)} ( \theta_{2} ) - \biggl[ \frac{2-\lambda}{2} \psi^{(n)} (u ) +\frac{\lambda }{2}\psi^{(n)} ( v ) \biggr] . \end{aligned}$$
(11)

By adding the inequalities of (10) and (11), we have

$$\begin{aligned} & \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac {2-\lambda}{2}v \biggr) \biggr) + \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda}{2}v \biggr) \biggr) \\ &\quad\leq2 \bigl( \psi^{(n)} ( \theta_{1} ) + \psi^{(n)} ( \theta _{2} ) \bigr) - \bigl( \psi^{(n)} ( u ) +\psi^{(n)} ( v ) \bigr) . \end{aligned}$$

Multiplying both sides by \(\lambda^{n-\frac{\alpha}{k}-1}\) in above and then integrating the resulting inequality with respect to λ over \([ 0,1 ]\), we have

$$\begin{aligned} & \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \biggl( \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) + \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda }{2}u+\frac{\lambda}{2}v \biggr) \biggr) \biggr) \,d \lambda \\ &\quad \leq \bigl\{ 2 \bigl( \psi^{(n)} ( \theta_{1} ) + \psi^{n} ( \theta_{2} ) \bigr) - \bigl( \psi^{(n)} ( u ) + \psi ^{(n)} ( v ) \bigr) \bigr\} \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1}\,d\lambda. \end{aligned}$$

This implies

$$\begin{aligned} &\frac{2^{n-\frac{\alpha}{k} } \varGamma_{k} ( n-\frac{\alpha}{k} ) }{ ( v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl( {}^{ c}D_{ ( \theta _{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{1}-u ) \\ &\qquad + ( -1 )^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta _{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta _{1}+\theta_{2}-v ) \bigr\} \\ &\quad\leq \bigl\{ 2 \bigl( \psi^{(n)} ( \theta_{1} ) + \psi ^{(n)} ( \theta_{2} ) \bigr) - \bigl( \psi^{(n)} ( u ) +\psi ^{(n)} ( v ) \bigr) \bigr\} \frac{1}{n-\frac{\alpha}{k} }. \end{aligned}$$
(12)

Multiplying (12) by \(\frac{ (n-\frac{\alpha}{k} )}{2}\),

$$\begin{aligned} &\frac{2^{n-\frac{\alpha}{k} -1} \varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} }} \bigl\{ \bigl({}^{ c}D_{ ( \theta _{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) \\ &\qquad + ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr\} \\ & \quad\leq \bigl( \psi^{(n)} ( \theta_{1} ) + \psi^{(n)} ( \theta _{2} ) \bigr) -\frac{\psi^{(n)} ( u ) +\psi^{(n)} ( v ) }{2}. \end{aligned}$$
(13)

Combining (9) and (13), we get (8). □

Remark 2

If we take \(k=1\) in Theorem 3, then it reduces to Theorem 3 in [14].

Lemma 1

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \)along with the assumptions in\(A_{1}\), then the following equality for Caputok-fractional derivatives holds:

$$ \begin{aligned}[b]&\frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-u ) +\psi^{(n)} ( \theta_{1}+\theta_{2}-v ) }{2}- \frac{\varGamma_{k} ( n-\frac{\alpha }{k} +k ) }{2 ( v-u ) ^{n-\frac{\alpha}{k} }} \\ &\qquad\times \bigl\{ \bigl({}^{ c}D_{ ( \theta_{1}+\theta_{2}-v ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) + ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-u ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr\} \\ &\quad= \frac{v-u}{2} \int_{0}^{1} \bigl( \lambda^{n-\frac{\alpha}{k} }- ( 1-\lambda ) ^{n-\frac{\alpha}{k} } \bigr) \psi^{(n+1)} \bigl( \theta_{1}+\theta_{2}- \bigl( \lambda u + ( 1-\lambda ) v \bigr) \bigr) \,d\lambda.\end{aligned} $$
(14)

Proof

It suffices to note that

$$ I=\frac{v-u}{2} \{ I_{1}-I_{2} \}, $$
(15)

where

$$\begin{aligned} I_{1}&= \int_{0}^{1} \bigl( \lambda^{n-\frac{\alpha}{k} } \bigr) \psi ^{(n+1)} \bigl( \theta_{1}+\theta_{2}- \bigl( \lambda u+ ( 1-\lambda ) v \bigr) \bigr) \,d\lambda \\ &= \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-u ) }{v-u} \\ &\quad -\frac{n-\frac{\alpha}{k} }{v-u} \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \psi^{(n)} \bigl( \theta _{1}+\theta_{2}- \bigl( \lambda u+ ( 1-\lambda ) v \bigr) \bigr) \,d\lambda \\ &= \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-u ) }{v-u} \\ &\quad - \frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} +1}} \bigl\{ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-u ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr\} \end{aligned}$$
(16)

and

$$\begin{aligned} I_{2}&= \int_{0}^{1} ( 1-\lambda ) ^{n-\frac{\alpha}{k} } \psi ^{(n+1)} \bigl( \theta_{1}+\theta_{2}- \bigl( \lambda u+ ( 1-\lambda ) v \bigr) \bigr) \,d\lambda \\ &= - \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-v ) }{v-u} \\ &\quad +\frac{n-\frac{\alpha}{k} }{v-u} \int_{0}^{1} ( 1-\lambda ) ^{n-\frac{\alpha}{k} -1} \psi^{(n)} \bigl( \theta_{1}+\theta_{2}- \bigl( \lambda u+ ( 1-t\lambda ) v \bigr) \bigr) \,d\lambda \\ &=- \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-v ) }{v-u} \\ &\quad + \frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha }{k} +1}} \bigl\{ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-v ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) \bigr\} . \end{aligned}$$
(17)

Combining (16) and (17) with (15) and get (14). □

Remark 3

If we take \(k=1\) in Lemma 1, then it reduces to Lemma 1 in [14].

Remark 4

If we take \(u=a\) and \(v=b\) in Lemma 1, then it reduces to Remark 2.5 in [11].

Lemma 2

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \)along with the assumptions in\(A_{1}\), then the following equality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha }{k} }} \\ &\qquad \times \bigl\{ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) + ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr\} \\ &\quad = \frac{v-u}{4} \biggl[ \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \,d\lambda \\ &\qquad - \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \psi ^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac {\lambda }{2}v \biggr) \biggr) \,d\lambda \biggr]. \end{aligned}$$
(18)

Proof

It suffices to note that

$$\begin{aligned} I=\frac{v-u}{4} \{ I_{1}-I_{2} \}, \end{aligned}$$
(19)

where

$$\begin{aligned} I_{1}&= \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \psi ^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{ 2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \,d\lambda \\ & = \frac{2}{v-u} \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac {u+v}{2} \biggr) \\ & \quad-\frac{2 ( n-\frac{\alpha}{k} ) }{v-u} \int_{0}^{1}\lambda^{n-\frac{\alpha }{k} -1} \psi^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \,d\lambda \\ & = \frac{2}{v-u} \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac {u+v}{2} \biggr) \\ &\quad - ( -1 ) ^{n}\frac{2^{n-\frac{\alpha}{k} +1}\varGamma_{k} ( n-\frac {\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} +1}} \bigl( {}^{ c}D_{ ( \theta _{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \end{aligned}$$
(20)

and

$$\begin{aligned} I_{2}&= \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \psi ^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda }{2}u+\frac{\lambda}{2}v \biggr) \biggr) \,d\lambda \\ &=- \frac{2}{v-u} \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) \\ &\quad+\frac{2 ( n-\alpha ) }{v-u} \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} -1} \psi ^{(n)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda}{2}v \biggr) \biggr) \,d\lambda \\ & = -\frac{2}{v-u} \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac {u+v}{2} \biggr) \\ &\quad+\frac{ 2^{n-\frac{\alpha}{k} +1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac{\alpha}{k} +1}} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac {u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ). \end{aligned}$$
(21)

Combining (20) and (21) with (19), we get (18). □

Remark 5

If we take \(k=1\) in Lemma 2, then it reduces to Lemma 2 in [14].

Remark 6

If we take \(u=a\) and \(v=b\) in Lemma 2, then it reduces to Lemma 2 in [10].

Theorem 4

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \). If\(|\psi^{(n+1)}|\)is a convex function on\([\theta_{1},\theta_{2}] \)along with the assumptions in\(A_{1}\), then the following inequality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \biggl\vert \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-u ) +\psi ^{(n)} ( \theta_{1}+\theta_{2}-v ) }{2}-\frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{2 ( v-u ) ^{n-\frac{\alpha}{k}}} \\ &\qquad\times \bigl( \bigl( {}^{ c}D_{ ( \theta _{1}+\theta_{1}-v ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-u ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr) \biggr\vert \\ &\quad\leq\frac{v-u}{n-\frac{\alpha}{k} +1} \biggl( 1-\frac{1}{2^{n-\frac {\alpha}{k} }} \biggr) \biggl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \\ & \qquad- \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert + \vert \psi^{(n+1)} ( v ) \vert }{2} \biggr) \biggr\} . \end{aligned}$$
(22)

Proof

By using Lemma 1 and the Jensen–Mercer inequality, we have

$$\begin{aligned} & \biggl\vert \frac{\psi^{(n)} ( \theta_{1}+\theta_{2}-u ) +\psi ^{(n)} ( \theta_{1}+\theta_{2}-v ) }{2}- \frac{\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{2 ( v-u ) ^{n-\frac{\alpha}{k} }} \\ &\quad\quad \times \bigl( \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-v ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) + ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2} -u ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr) \biggr\vert \\ &\quad \leq\frac{v-u}{2} \int_{0}^{1} \bigl\vert \lambda^{n-\frac{\alpha}{k} }- ( 1-\lambda ) ^{n-\frac{\alpha}{k} } \bigr\vert \bigl\vert \psi^{(n+1)} \bigl( \theta _{1}+\theta_{2} \\ &\qquad - \bigl( \lambda u+ ( 1-\lambda ) v \bigr) \bigr) \bigr\vert \,d \lambda \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert \\ &\quad \leq\frac{v-u}{2} \int_{0}^{1} \biggr\{ \bigl\vert \lambda^{n-\frac{\alpha}{k} }- ( 1-\lambda ) ^{n-\frac{\alpha}{k} } \bigr\vert \\ &\qquad + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert - \bigl( \lambda \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert + ( 1-\lambda ) \bigl\vert \psi ^{(n+1)} ( v ) \bigr\vert \bigr) \biggr\} \,d\lambda \\ &\quad \leq\frac{v-u}{2} [ I_{1}+I_{2} ], \end{aligned}$$
(23)

where

$$\begin{aligned} I_{1} =& \int_{0}^{\frac{1}{2}} \bigl( ( 1-\lambda ) ^{n-\frac {\alpha}{k} }-\lambda^{n-\frac{\alpha}{k} } \bigr) \\ &{} \times \bigl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert - \bigl( \lambda \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert + ( 1-\lambda ) \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \bigr) \bigr\} \,d\lambda \\ =& \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \bigr) \biggl( \frac{1}{ n-\frac{\alpha}{k} +1}-\frac{2^{-n+\frac{\alpha}{k} }}{n-\frac{\alpha }{k} +1} \biggr) \\ &{}- \biggl\{ \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) }-\frac{2^{-n+\frac{\alpha}{k} -1}}{n-\frac {\alpha}{k} +1} \biggr) \\ &{}+ \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \biggl( \frac{1}{ ( n-\frac{\alpha }{k} +2 ) }-\frac{2^{-n+\frac{\alpha}{k} -1}}{n-\frac{\alpha}{k} +1} \biggr) \biggr\} \end{aligned}$$
(24)

and

$$\begin{aligned} I_{2} =& \int_{\frac{1}{2}}^{1} \bigl( \lambda^{n-\frac{\alpha}{k} }- ( 1-\lambda ) ^{n-\frac{\alpha}{k} } \bigr) \\ &{}\times \bigl\{ \bigl\vert \psi ^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert - \bigl( \lambda \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert + ( 1-\lambda ) \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \bigr) \bigr\} \,d\lambda \\ =& \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \bigr) \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +1 ) }-\frac{2^{-n+\frac{\alpha}{k} }}{n-\frac{\alpha}{k} +1} \biggr) \\ &{}- \biggl\{ \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +2 ) }-\frac{ 2^{-n+\frac{\alpha}{k} -1}}{n-\frac{\alpha}{k} +1} \biggr) \\ &{}+ \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac {\alpha}{k} +2 ) }-\frac{2^{-n+\frac{\alpha}{k} -1}}{n-\frac{\alpha}{k} +1} \biggr) \biggr\} . \end{aligned}$$
(25)

Combining (24) and (25) with (23) and we get (22). This completes the proof. □

Remark 7

If we take \(k=1\) in Theorem 4, then it reduces to Theorem 4 in [14].

Remark 8

If we take \(u=a\) and \(v=b\) in Theorem 4, then it reduces to Corollary 2.7 in [11].

Theorem 5

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \). If\(|\psi^{(n+1)}|\)is a convex function on\([\theta_{1},\theta_{2}] \)along with the assumptions in\(A_{1}\), then the following inequality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac{u+v}{2} \biggr) - \frac{2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad{}\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v }{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ & \quad\leq\frac{v-u}{2 ( n-\frac{\alpha}{k} +1 ) } \biggl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \\ &\qquad{} - \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert + \vert \psi^{(n+1)} ( v ) \vert }{2} \biggr) \biggr\} . \end{aligned}$$
(26)

Proof

By using Lemma 2 and the Jensen–Mercer inequality, we have

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma ( n-\frac{\alpha}{k} +1 ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v }{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ &\quad\leq\frac{v-u}{4} \biggl[ \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert \,d\lambda \\ &\qquad - \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac {\lambda }{2}v \biggr) \biggr) \biggr\vert \,d\lambda \biggr] \\ & \quad\leq\frac{v-u}{4} \biggl[ \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \biggl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert \\ & \qquad+ \bigl\vert \psi ^{(n+1)} ( \theta_{2} ) \bigr\vert - \biggl( \frac{\lambda}{2} \bigl\vert \psi ^{(n+1)} ( u ) \bigr\vert +\frac{ ( 2-\lambda ) }{2} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \biggr) \biggr\} \,d\lambda \\ &\qquad + \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} } \biggl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \\ & \qquad- \biggl( \frac{ ( 2-\lambda ) }{2} \bigl\vert \psi ^{(n+1)} ( u ) \bigr\vert +\frac{\lambda}{2} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert \biggr) \biggr\} \,d\lambda \biggr] \\&\quad\quad\text{by using calculus tools, we obtain} \\ &\quad\leq\frac{v-u}{2 ( n-\frac{\alpha}{k} +1 ) } \biggl\{ \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert \\ &\qquad - \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert + \vert \psi^{(n+1)} ( v ) \vert }{2} \biggr) \biggr\} . \end{aligned}$$

This completes the proof. □

Remark 9

If we take \(k=1\) in Theorem 5, then it reduces to Theorem 5 in [14].

Theorem 6

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \). If\(|\psi^{(n+1)}|^{q}\)is a convex function on\([\theta_{1},\theta _{2}]\), \(q>1\)and along with the assumptions in\(A_{1}\), then the following inequality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac{u+v}{2} \biggr) - \frac{2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad{}\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v }{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+2-v ) \bigr] \biggr\vert \\ & \quad\leq\frac{v-u}{4} \biggl( \frac{1}{np-\frac{\alpha}{k} p+1} \biggr) ^{\frac{1}{p}} \biggl[ \biggl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \\ &\qquad{}- \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert ^{q} +3 \vert \psi^{(n+1)} ( v ) \vert ^{q} }{4} \biggr) \biggr) ^{\frac{1}{q}}+ \biggl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi ^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \\ &\qquad{} - \biggl( \frac{3 \vert \psi^{(n+1)} ( u ) \vert ^{q} + \vert \psi^{(n+1)} ( v ) \vert ^{q} }{4} \biggr) \biggr) ^{\frac{1}{q}} \biggr]. \end{aligned}$$
(27)

Proof

By using Lemma 2 and applying the Hölder integral inequality, we have

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ &\quad \leq\frac{v-u}{4} \biggl[ \biggl( \int_{0}^{1}\lambda^{ ( n-\frac {\alpha}{k} ) p} \,d\lambda \biggr) ^{\frac{1}{p}} \biggl( \int_{0}^{1} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac {2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \\ & \qquad+ \biggl( \int_{0}^{1}\lambda^{ ( n-\frac{\alpha}{k} ) p} \,d\lambda \biggr) ^{\frac{1}{p}} \biggl( \int _{0}^{1} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac {\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \biggr]. \end{aligned}$$

By the convexity of \(|\psi^{(n+1)}|^{q}\), we have

$$\begin{aligned} \begin{aligned} & \leq\frac{v-u}{4} \biggl( \frac{1}{np-\frac{\alpha}{k} p+1} \biggr) ^{\frac{1}{p}} \biggl[ \biggl\{ \int_{0}^{1} \biggl( \bigl\vert \psi ^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \\ &\quad- \biggl( \frac{\lambda}{2} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q}+\frac{2-\lambda}{2} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \biggr) \,d \lambda \biggr\} ^{\frac{1}{q}} + \biggl\{ \int_{0}^{1} \biggl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} \\ &\quad+ \bigl\vert \psi ^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q}- \biggl( \frac{2-\lambda}{2} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q}+\frac{\lambda}{2} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \biggr) \,d\lambda \biggr\} ^{\frac{1}{q}} \biggr] \\ & \leq\frac{v-u}{4} \biggl( \frac{1}{np-\frac{\alpha}{k} p+1} \biggr) ^{\frac{1}{p}} \biggl[ \biggl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \\ &\quad- \biggl( \frac{ \vert \psi^{n+1} ( u ) \vert ^{q} +3 \vert \psi^{(n+1)} ( v ) \vert ^{q} }{4} \biggr) \biggr) ^{\frac{1}{q}} \\ &\quad + \biggl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi ^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q}- \biggl( \frac{3 \vert \psi^{(n+1)} ( u ) \vert ^{q} + \vert \psi^{(n+1)} ( v ) \vert ^{q} }{4} \biggr) \biggr) ^{\frac{1}{q}} \biggr].\end{aligned} \end{aligned}$$

This completes the proof. □

Remark 10

If we take \(k=1\) in Theorem 6, then it reduces to Theorem 6 in [14].

New Hölder and improved İşcan inequalities

Theorem 7

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(0\leq \theta_{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \). If\(|\psi^{(n+1)}|^{q}\)is a convex function on\([\theta_{1},\theta _{2}]\), \(q>1\)and along with the assumptions in\(A_{1}\), then the following inequality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+\theta_{2}-\frac{u+v}{2} \biggr) - \frac{2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ & \qquad{}\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ & \quad \leq\frac{v-u}{4} \biggl[ \biggl\{ \biggl( \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+1 ) ( ( n-\frac{\alpha}{k} ) p+2 ) } \biggr) ^{\frac{1}{p}} \biggl( \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} \\ &\qquad{} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr)- \biggl( \frac{1}{12} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} + \frac{5}{12} \bigl\vert \psi^{(n+1)} (v ) \bigr\vert ^{q} \biggr) \biggr) ^{\frac{1}{q}} \\ &\qquad{} + \biggl( \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+2 ) } \biggr) ^{\frac{1}{p}} \biggl( \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi ^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr) \\ &\qquad{} - \biggl( \frac{1}{6} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac{1}{3} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \biggr) ^{\frac{1}{q}} \biggr\} \\ &\qquad{} + \biggl\{ \biggl( \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+1 ) ( ( n-\frac{\alpha}{k} ) p+2 ) } \biggr) ^{\frac{1}{p}} \\ & \qquad{}\times \biggl( \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr) - \biggl( \frac {5}{12} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac {1}{12} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \biggr) ^{\frac{1}{q}} \\ &\qquad{} + \biggl( \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+2 ) } \biggr) ^{\frac {1}{p}} \biggl( \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{n+1} ( \theta_{2} ) \bigr\vert ^{q} \bigr) \\ & \qquad{}- \biggl( \frac{1}{3} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac {1}{6} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \biggr) ^{\frac{1}{q}} \biggr\} \biggr]. \end{aligned}$$
(28)

Proof

By using Lemma 2 with Jensen–Mercer inequality and applying the Hölder–İşcan integral inequality [Theorem 1.4, [15]], we have

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u ) + ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac {u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ &\quad\leq\frac{v-u}{4} \biggl\{ \biggl( \int_{0}^{1} ( 1-\lambda ) \lambda^{np-\frac{\alpha}{k} p} \, d\lambda \biggr) ^{\frac{1}{p}} \\ &\qquad \times \biggl( \int_{0}^{1} ( 1-\lambda ) \biggl\vert \psi^{(n+1)} \biggl( \theta _{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \\ &\qquad+ \biggl( \int _{0}^{1}\lambda^{np-\frac{\alpha}{k} p+1} \,dt \biggr) ^{\frac{1}{p}} \biggl( \int_{0}^{1}\lambda \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \, d\lambda \biggr) ^{\frac{1}{q}} \biggr\} \\ &\qquad + \biggl\{ \biggl( \int_{0}^{1} ( 1-\lambda ) \lambda^{np-\frac {\alpha}{k} p} \,d\lambda \biggr) ^{\frac{1}{p}} \biggl( \int_{0}^{1} ( 1-\lambda ) \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2} \\ &\qquad- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda }{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \\ &\qquad+ \biggl( \int_{0}^{1}\lambda^{np-\frac{\alpha}{k} p+1} \,d\lambda \biggr) ^{\frac{1}{p}} \biggl( \int_{0}^{1}\lambda \biggl\vert \psi ^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda }{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \biggr\} . \end{aligned}$$
(29)

By the convexity of \(|\psi^{(n+1)}|^{q}\)

$$\begin{aligned} & \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda }{2}u+ \frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \\ &\quad\leq \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q}+ \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q}- \biggl( \frac{\lambda}{2} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q}+\frac{2-\lambda}{2} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr). \end{aligned}$$
(30)

It is easy to see that

$$\begin{aligned} \int_{0}^{1} ( 1-\lambda ) \lambda^{np-\frac{\alpha}{k}p} \, d\lambda= \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+1 ) ( ( n-\frac{\alpha}{k} ) p+2 ) } \end{aligned}$$
(31)

and

$$\begin{aligned} & \int_{0}^{1} ( 1-\lambda ) \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad = \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr) \\ &\qquad{} - \biggl( \frac{1}{12} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac{5}{12} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \end{aligned}$$
(32)

and

$$\begin{aligned} \int_{0}^{1}\lambda^{np-\frac{\alpha}{k} p+1} \,d \lambda= \frac{1}{ ( ( n-\frac{\alpha}{k} ) p+2 ) } \end{aligned}$$
(33)

and

$$\begin{aligned} & \int_{0}^{1}\lambda \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta _{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad=\frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr) - \biggl( \frac {1}{6} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac{1}{3} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \end{aligned}$$
(34)

and

$$\begin{aligned} & \int_{0}^{1} ( 1-\lambda ) \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad=\frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi^{(n+1)} ( \theta_{2} ) \bigr\vert ^{q} \bigr) - \biggl( \frac {5}{12} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac {1}{12} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \end{aligned}$$
(35)

and

$$\begin{aligned} & \int_{0}^{1}\lambda \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta _{2}- \biggl( \frac{2-\lambda}{2}u+\frac{\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad= \frac{1}{2} \bigl( \bigl\vert \psi^{(n+1)} ( \theta_{1} ) \bigr\vert ^{q} + \bigl\vert \psi ^{n+1} ( \theta_{2} ) \bigr\vert ^{q} \bigr) - \biggl( \frac{1}{3} \bigl\vert \psi^{(n+1)} ( u ) \bigr\vert ^{q} +\frac{1}{6} \bigl\vert \psi^{(n+1)} ( v ) \bigr\vert ^{q} \biggr) \end{aligned}$$
(36)

By combining (31), (32), (33), (34), (35), (36), with (29) we get (28).

This completes the proof. □

Remark 11

If we take \(k=1\) in Theorem 7, then it reduces to Theorem 7 in [14].

Theorem 8

Suppose that\(\psi: [ \theta_{1},\theta_{2} ] \rightarrow R\)is a differentiable mapping on\((\theta_{1},\theta_{2} )\)with\(\theta _{1}<\theta_{2}\)and\(\psi\in C^{n+1} [ \theta_{1},\theta_{2} ] \). If\(|\psi^{(n+1)}|^{q}\)is a convex function on\([\theta_{1},\theta_{2}]\), \(q\geq1\)and along with the assumptions in\(A_{1}\), then the following inequality for Caputok-fractional derivatives holds:

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +k ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\qquad\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ &\quad\leq\frac{v-u}{4} \biggl\{ \biggl\{ \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) } \biggr) ^{1-\frac{1}{q}} \\ &\qquad \times \biggl( \frac{ \vert \psi^{n+1} ( \theta_{1} ) \vert ^{q} + \vert \psi^{n+1} ( \theta_{2} ) \vert ^{q}}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) }- \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha }{k} +3 ) } \\ &\quad\quad +\frac{(n-\frac{\alpha}{k}+5) \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \biggr) \biggr) ^{\frac{1}{q}} \\ &\qquad + \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +2 ) } \biggr) ^{1-\frac{1}{q}} \biggl( \frac{ \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q}}{ ( n-\frac{\alpha}{k} +2 ) } \\ &\quad\quad - \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +3 ) } +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha }{k} +3 ) } \biggr) \biggr) ^{\frac{1}{q}} \biggr\} \\ &\qquad + \biggl\{ \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac {\alpha}{k} +2 ) } \biggr) ^{1-\frac{1}{q}} \\ &\qquad \times \biggl( \frac{ \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q}}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) }- \biggl( \frac{ ( n-\frac{\alpha}{k} +5 ) \vert \psi^{n+1} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +1 ) ( n-\frac {\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \\ &\qquad +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac {\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \biggr) \biggr) ^{\frac{1}{q}}+ \biggl( \frac{1}{ ( n-\frac{\alpha}{k} +2 ) } \biggr) ^{1-\frac{1}{q}} \\ &\qquad\times \biggl( \frac{ \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q}}{ ( n-\frac{\alpha}{k} +2 ) } \\ &\qquad - \biggl( \frac{ ( n-\frac{\alpha}{k} +4 ) \vert \psi ^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac {\alpha}{k} +3 ) } +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +3 ) } \biggr) \biggr) ^{\frac {1}{q}} \biggr\} \biggr\} . \end{aligned}$$
(37)

Proof

By using Lemma 2 with the Jensen–Mercer inequality and applying the improved power-mean integral inequality [Theorem1.5, [15]], we have

$$\begin{aligned} & \biggl\vert \psi^{(n)} \biggl( \theta_{1}+ \theta_{2}-\frac{u+v}{2} \biggr) -\frac {2^{n-\frac{\alpha}{k} -1}\varGamma_{k} ( n-\frac{\alpha}{k} +1 ) }{ ( v-u ) ^{n-\frac {\alpha}{k} }} \\ &\quad\quad\times \bigl[ \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{+}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-u )+ ( -1 ) ^{n} \bigl( {}^{ c}D_{ ( \theta_{1}+\theta_{2}-\frac{u+v}{2} ) ^{-}}^{\alpha,k } \psi \bigr) ( \theta_{1}+\theta_{2}-v ) \bigr] \biggr\vert \\ &\quad\leq\frac{v-u}{4} \biggl\{ \biggl( \int_{0}^{1} ( 1-\lambda ) \lambda^{n-\frac{\alpha}{k} } \, d\lambda \biggr) ^{1-\frac{1}{q}} \\ &\qquad \times \biggl( \int_{0}^{1} ( 1-\lambda )\lambda^{n-\frac{\alpha}{k}} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{\lambda}{2}u+\frac {2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr)^{\frac {1}{q}} \\ & \qquad+ \biggl( \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} +1} \,d\lambda \biggr) ^{1-\frac{1}{q}} \biggl( \int_{0}^{1}\lambda^{n-\frac{\alpha}{k}+1} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2} \\ &\qquad- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \biggr) ^{\frac{1}{q}} \biggr\} \\ &\qquad + \biggl\{ \biggl( \int_{0}^{1} ( 1-\lambda ) \lambda^{n-\frac{\alpha}{k} } \, d\lambda \biggr) ^{1-\frac{1}{q}} \biggl( \int_{0}^{1} ( 1-\lambda )\lambda^{n-\frac{\alpha}{k}} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2} \\ &\qquad- \biggl( \frac{\lambda}{2}v+\frac{2-\lambda}{2}u \biggr) \biggr) \biggr\vert ^{q} \,d \lambda \biggr)^{\frac {1}{q}}+ \biggl( \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} +1} \,d\lambda \biggr) ^{1-\frac{1}{q}} \\ &\qquad\times \biggl( \int_{0}^{1}\lambda^{n-\frac{\alpha}{k}+1} \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{\lambda}{2}v+\frac{2-\lambda}{2}u \biggr) \biggr) \biggr\vert ^{q} \,dt \biggr) ^{\frac{1}{q}} \biggr\} . \end{aligned}$$
(38)

It is easy to see that

$$\begin{aligned} \int_{0}^{1} ( 1-\lambda ) \lambda^{n-\frac{\alpha}{k}} \, d\lambda= \frac{1}{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) } \end{aligned}$$
(39)

and

$$ \begin{aligned}[b] & \int_{0}^{1} ( 1-\lambda ) \lambda^{n-\frac{\alpha}{k} } \biggl\vert \psi^{n+1} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{\lambda}{2}u+ \frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad= \frac{ ( \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q} ) }{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) } \\ &\qquad- \biggl( \frac{ \vert \psi^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac {\alpha}{k} +3 ) } +\frac{ ( n-\frac{\alpha}{k} +5 ) \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac {\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \biggr)\end{aligned} $$
(40)

and

$$\begin{aligned} \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} +1} \,d \lambda= \frac{1}{ ( n-\frac{\alpha}{k} +2 ) } \end{aligned}$$
(41)

and

$$\begin{aligned} & \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} +1} \biggl\vert \psi ^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{\lambda}{2}u+\frac{2-\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad= \frac{ ( \vert \psi^{(n+1)} ( \theta _{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q} ) }{ ( n-\frac{\alpha}{k} +2 ) } \\ &\quad\quad{}- \biggl( \frac{ \vert \psi ^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +3 ) } +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \biggr) \end{aligned}$$
(42)

and

$$\begin{aligned} & \int_{0}^{1} ( 1-\lambda ) \lambda^{n-\frac{\alpha }{k} } \biggl\vert \psi^{(n+1)} \biggl( \theta_{1}+\theta_{2}- \biggl( \frac{2-\lambda}{2}u+ \frac {\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad = \frac{ ( \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q} ) }{ ( n-\frac{\alpha}{k} +1 ) ( n-\frac{\alpha}{k} +2 ) } \\ &\qquad{} - \biggl( \frac{ ( n-\frac{\alpha}{k} +5 ) \vert \psi^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +1 ) ( n-\frac {\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac{\alpha}{k} +3 ) } \biggr) \end{aligned}$$
(43)

and

$$\begin{aligned} & \int_{0}^{1}\lambda^{n-\frac{\alpha}{k} +1} \biggl\vert \psi ^{(n+1)} \biggl( \theta_{1}+ \theta_{2}- \biggl( \frac{2-\lambda}{2}u+\frac {\lambda}{2}v \biggr) \biggr) \biggr\vert ^{q} \,d\lambda \\ &\quad= \biggl( \frac{ \vert \psi^{(n+1)} ( \theta_{1} ) \vert ^{q} + \vert \psi^{(n+1)} ( \theta_{2} ) \vert ^{q}}{ ( n-\frac {\alpha}{k} +2 ) } \\ &\qquad{}- \biggl( \frac{ ( n-\frac{\alpha}{k} +4 ) \vert \psi^{(n+1)} ( u ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +2 ) ( n-\frac {\alpha}{k} +3 ) } +\frac{ \vert \psi^{(n+1)} ( v ) \vert ^{q}}{2 ( n-\frac{\alpha}{k} +3 ) } \biggr) \biggr). \end{aligned}$$
(44)

By combining (39), (40), (41), /(42), (43), (44) with (38) we get (37), which completes the proof. □

Conclusion

In this article, we show Hermite–Hadamard type inequalities can be expressed in Caputo k-fractional derivative form by employing the Jensen–Mercer inequality. New Hermite–Jensen–Mercer type inequalities using Caputo k-fractional derivatives are established for differentiable mappings whose derivatives in absolute values are convex. Some known results are recaptured as special cases of our results. We hope that our new idea and technique may inspire many researcher in this fascinating field.

References

  1. 1.

    Ali, M.M., Khan, A.R.: Generalized integral Mercer’s inequality and integral means. J. Inequal. Spec. Funct. 10(1), 60–76 (2019)

    MathSciNet  Google Scholar 

  2. 2.

    Kian, M., Moslehian, M.S.: Refinements of the operator Jensen Mercer inequality. Electron. J. Linear Algebra 26, 742–753 (2013)

    MathSciNet  Article  Google Scholar 

  3. 3.

    Cho, Y.J., Matic, M., Pečarić, J.: Two mappings in connection to Jensen inequality. Panam. Math. J. 12, 43–50 (2002)

    MathSciNet  MATH  Google Scholar 

  4. 4.

    Matkovic, A., Pečarić, J., Perić, I.: A variant of Jensens inequality of Mercer’s type for operators with applications. Linear Algebra Appl. 418(2–3), 551–564 (2006)

    MathSciNet  Article  Google Scholar 

  5. 5.

    Abramovich, S., Baric, J., Pečarić, J.: A variant of Jessens inequality of Mercers type for superquadratic functions. J. Inequal. Pure Appl. Math. 9(3), Article ID 62 (2008)

    MathSciNet  MATH  Google Scholar 

  6. 6.

    Baric, J., Matkovic, A.: Bounds for the normalized Jensen Mercer functional. J. Math. Inequal. 3(4), 529–541 (2009)

    MathSciNet  Article  Google Scholar 

  7. 7.

    Furuta, T., Micic, H., Pečarić, J., Seo, Y.: Mond Pecaric Method in Operator Inequalities, Element, Zagreb (2005)

    Google Scholar 

  8. 8.

    Li, C.P., Deng, W.H.: Remarks on fractional derivatives. Appl. Math. Comput. 187(2), 777–784 (2007)

    MathSciNet  MATH  Google Scholar 

  9. 9.

    Kilbas, A.A., Srivastava, H.M., Trujillo, J.J.: Theory and Applications of Fractional Derivatial Equations. North-Holland Math. Stud. Elsevier, Amsterdam (2006)

    Google Scholar 

  10. 10.

    Farid, G., Naqvi, S., Rehman, A.U.: A version of the Hadamard inequality for Caputo fractional derivatives and related results. RGMIA Res. Rep. Collect. 20, Article ID 59 (2017)

    Google Scholar 

  11. 11.

    Naqvi, S., Farid, G., Tariq, B.: Caputo fractional integral inequalities via m convex function. RGMIA Res. Rep. Collect. 20, Article ID 113 (2017)

    Google Scholar 

  12. 12.

    Diaz, R., Pariguan, E.: On hypergeometric functions and Pochhammer k-symbol. Divulg. Mat. 15(2), 179–192 (2007)

    MathSciNet  MATH  Google Scholar 

  13. 13.

    Farid, G., Javed, A., Rehman, A.: On Hadamard inequalities for n-times differentiable functions which are relative convex via Caputo k-fractional derivatives. Nonlinear Anal. Forum 22(2), 17–28 (2014)

    MathSciNet  MATH  Google Scholar 

  14. 14.

    Zaho, I., Butt, S.I., Nasir, J., Wang, Z., Tlili, I.: Hermite–Jensen–Mercer type inequalities for Caputo fractional derivatives. J. Funct. Spaces (2020). https://doi.org/10.1155/2020/7061549

    MathSciNet  Article  MATH  Google Scholar 

  15. 15.

    Özcan, S., İmdat, İ.: Some new Hermite–Hadamard type inequalities for s-convex functions and their applications. J. Inequal. Appl. 2019(1), Article ID 201 (2019)

    MathSciNet  Article  Google Scholar 

Download references

Acknowledgements

The authors are thankful to the reviewers for their valuable comments.

Availability of data and materials

All data required for this paper is included within this paper.

Funding

This work was sponsored in part by The Key Research Base Project of Sichuan Provincial Education Department(KJJR2019-001);the Sichuan Provincial Philosophy and Social Science Planning Project of China(SC19B110);the Sichuan Provincial Quality Engineering Project(2019JWC024). The research of Saad Ihsan Butt has been fully supported by H.E.C. of Pakistan under NPRU project 7906.

Author information

Affiliations

Authors

Contributions

All authors contribute equally in this paper. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Ya Liu.

Ethics declarations

Competing interests

The authors do not have any competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Zhao, S., Butt, S.I., Nazeer, W. et al. Some Hermite–Jensen–Mercer type inequalities for k-Caputo-fractional derivatives and related results. Adv Differ Equ 2020, 262 (2020). https://doi.org/10.1186/s13662-020-02693-y

Download citation

Keywords

  • Convex functions
  • Hermite–Hadamard inequalities
  • Jensen inequality
  • Jensen–Mercer inequality
  • k-Caputo fractional derivatives
\